PROFIL HASIL BELAJAR KONSEP ENERGI PADA MAHASISWA PPL TAHUN 2020/2021 PRODI FISIKA UNIVERSITAS CENDERAWASIH - Selina, Nambe; Virman, Virman; Silaban, Adeline (Papua Journal of Physics Education, 2023)
Research has been carried out with the aim of knowing how the profile of PPL student learning outcomes on the concept of energy. This type of research is quantitative with pre-experimental design research method, the form of design used is one-group pretest-posttest. The analysis technique used is validity and reliability. The results of the research and data processing were obtained: 1) there were quite good student learning outcomes with an average value, namely the first concept was worth 77.35, the second concept was worth 77.14 and the third concept was worth 79.05, so the PPL student learning outcomes in 2021/2022 in the concept of energy is said to be good